An efficiency analysis of projects using DEA - Ku-Mahamud, Ku Ruhana; Mat Kasim, Maznah; Abd Ghani, Nor Farzana; Abdullah, Fader (EuroJournal Publishing, Inc., 2011)
This paper presents a model to measure the efficiency of products produced by organization.The products are the projects carried out by the selected organization.The model which has been developed was based on data envelopment analysis, optimizes a ratio of multiple weighted outputs to a multiple weighted inputs.This non-parametric model is simple and yet very powerful because it can consider multiple outputs and inputs simultaneously. Descriptive analysis of the data, relative efficiency results, peer group analysis and projection for inefficient projects are presented.The proposed efficiency model is simple and practical in implementation.It is hope that the projects which act as the decision making unit can later be used to determine the efficiency of the company department/unit that housed the projects.